NILAI PENDIDIKAN KARAKTER TOKOH NASIONAL DALAM TEKS BIOGRAFI KARYA SISWA KELAS X - Sari, Vio Kurnia; Ariani, Dewi (Hasta Wiyata, 2026)
This study aims to examine the character representation in biographical texts written by tenth-grade vocational high school students based on three dimensions of character education: moral knowledge, moral feeling, and moral action. The study is motivated by the tendency of biographical text learning to focus primarily on structural and linguistic aspects, while the value dimension and character construction have not been systematically analyzed. Previous studies on character education in texts have generally emphasized the identification of value types or the use of biographical texts as instructional materials, rather than examining students’ written products as reflective constructions of moral values. Consequently, there is still limited empirical research that explores how students represent and integrate moral dimensions within their own biographical writing. This research employs a qualitative approach with a descriptive method. The data consist of students’ biographical texts obtained through document analysis and are analyzed through data reduction, data display, and conclusion drawing. The results indicate that character representation reflects the integration of the three dimensions. Moral knowledge is shown through the understanding of right and wrong values, moral feeling is reflected in empathy and concern, while moral action is demonstrated through behaviors such as responsibility, hard work, and integrity. These findings suggest that biographical texts not only reflect literacy skills but also serve as a medium for constructing and internalizing moral values, contributing to the development of character-based Indonesian language learning.